Sleep matters: The association of race, bedtime, outdoor time, and physical activity with preschoolers' sleep - Allison A. Parsons; Nicholas J. Ollberding; Laurie Smith; Kristen A. Copeland (Preventive Medicine Reports, 2018)
Sleep is necessary for optimal functioning. Little is known about the extent to which race and opportunities to be active influence sleep in preschool-aged children attending full-day child care. Participants (n = 359) in this cross-sectional study attended 30 randomly selected, childcare centers in Cincinnati, OH. Data collection occurred from November 2009 to January 2011. Hierarchical linear regression and generalized estimating equations tested for associations between nighttime sleep duration and race, outdoor/indoor active time, actual physical activity (PA), screen time, daytime nap, and bedtime after 9 pm. Participants slept a mean ± SD of 1.5 ± 0.8 h at childcare and 9.7 ± 1.0 h at bedtime. White children (β = 0.57 ± 0.14, p < 0.01) and children identifying as Other race (β = 0.40 ± 0.15, p < 0.01) slept more hours than Black children at nighttime. White children were less likely to nap at childcare than Black children. Inside PA time provided was associated with increased nighttime sleep duration (β = 0.092 ± 0.04 h per 30 min PA, p < 0.03). There was no association between outdoor time or moderate to vigorous PA and nighttime sleep. Black children slept less at night on average, but were more likely to engage in nap sleep at childcare resulting in similar overall sleep duration. Additional studies in diverse populations that explore the effects of nighttime versus nap time sleep on child health and well-being are needed. Keywords: Sleep, Childcare, Race, Physical activity, Preschool aged children